A study on superficial veins of upper limb - T K Vasudha (Wolters Kluwer Medknow Publications, 2013)
Background : It is quite common to find many variations in the distribution of superficial veins in the body. Veins of the upper limbs are variable in number and position.The superficial veins are clinically important and are used for venaepuncture, transfusion and cardiac catheterization. Aim : The present study was mainly concentrated on cephalic, basilic and median cubital veins. The purpose of this study is to review the origin, course, termination and variations of these veins, as these veins play an important role in diagnostic, therapeutic and surgical procedures. Material and methods: The material used for the present study included twentyfive cadavers, from the department of Anatomy, Narayana Medical College (NMC), Nellore, and one hundred first MBBS students of NMC, Nellore. The data obtained from present study was compared with similar studies available in literature. Result: The various patterns of venous anastomoses observed in cubital fossa could be grouped into five types ie., Type I to Type V. Type I - was found in 88% of the cadavers and in 96% of living subjects. Type II -was found in 4% of the cadavers, Type III- in 2% of cadavers, and 4% of living subjects, Type IV- was found in 4% of cadavers, ans Type V- in 2% of living subjects. Conclusion: Knowledge of the patterns of superficial veins in cubital fossa is essential for clinicians, since they play an important role in diagnostic as well as therapeutic procedures.